Photocatalysis of Sago Wastewater using Sago Starch-Tio2 Films - Rubiyah, Baini; Sariah, Abang (SCOPE Publication, 2024)
his work is about wastewater treatment using sago starch-TiO2 hybrid film. The surface morphology of the films was evaluated using Scanning Electron Microscopy (SEM), and the analysis of the sago wastewater treatment films was in terms of the Biological Oxygen Demand (BOD), Chemical Oxygen Demand (COD) and Total Suspended Solid (TSS). Pseudo first order kinetic model was also included in the analysis. Findings show that the TiO2 particles were embedded well within the starch matrix. White spots were observed on the SEM images indicating the distribution of TiO2 particles on the surface of the films. The ability of the films to treat sago wastewater was observed by the percentage reduction of BOD, COD and TSS, which were estimated to be about 80% and 60% for the photocatalysis under controlled UV light of 40 watts and under the sunlight, respectively. The Pseudo First Order kinetic model fit well onto the experimental data with mean square error of 2.3- 2.5 indicating the suitabilty of this model to predict the changes of BOD, COD and TSS with time. The constant, k, was estimated to be 0.0074.